Peculiarities of Lipid Spectrum in Children with short stature - Kopytina E.V. (Саратовский научно-медицинский журнал, 2010)
The research goal is to examine the lipid spectrum and to evaluate the effectiveness of somatropin therapy for correcting metabolic disorders in children with various forms of short stature. 60 children (30 with growth hormone deficiency and 30 with constitutional delayed growth) have been examined. Total cholesterol, low-density lipoprotein, high-density lipoprotein in blood serum have been studied before treatment and after one year of somatropin therapy. Atherogenic coefficient has been calculated. The results have been compared with the control group. Dyslipidemia characterized by increase of total cholesterol level (4.70±1.51 mmol/l) and low-density lipoprotein (2.46±1.04 mmol/l) has been found in children with growth hormone deficiency. 13.3% of those children had increased atherogenic coefficient. Increase of low-density lipoprotein level (2.64±0.39 mmol/l) and of high-density lipoprotein level (1.96±0.56 mmol/l) in children with constitutional delayed growth has been observed. Due to somatropin therapy these indicators have been normalized within the year in patients of both groups. Dyslipidemia remained stable in children with constitutional delayed growth, who did not receive somatropin treatment. The influence of growth hormone deficiency on dyslipidemia development in children with short stature and effectiveness of somatropin therapy for correcting lipids disorders have been demonstrated